“Com o olho em punho”: o cinema superoitista de Torquato Neto - Barreto, Moema Pascoini (Universidade Federal de São Carlos, 2017)
This research intends to explore the filmmaking activities of Torquato Neto in the beginning of the 70´s. Throughout his artistic life course, Torquato crossed diferent sorts of media, producing and stimulating Brazilian independent culture. During the last three years of his life, he accomplished what we call turn to cinema, the period we´ll analyze in this dissertation. We'll start analyzing the relation between the movies Nosferato no Brasil (Ivan Cardoso, 1971), Helô e Dirce (Luiz Otávio Pimentel, 1972), Terror na Vermelha (Torquato Neto, 1972) and the writings from the Geléia Geral column in the newspaper Última Hora, published between august 1971 and march 1972. Besides the relation between this works, Torquato Neto´s actions as a booster agent for the super-8 production throughout the 70´s will be discussed.
Keywords: Torquato Neto; Cinema brasileiro; Super-8; Torquato Neto; Brazilian cinema; Super-8; CIENCIAS HUMANAS; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO